Exhausted Heart Rate Responses to Repeated Psychological Stress in Women With Major Depressive Disorder - Schiweck, Carmen; Gholamrezaei, Ali; Hellyn, Maxim; Vaessen, Thomas; Vrieze, Elske; Claes, Stephan (Frontiers in Psychiatry, 2022)
Past research links depression and blunted cardiac vagal reactivity to chronic stress. Yet, to our knowledge no experiment investigates heart rate (variability) responses to a repeated laboratory stressor in patients with depression. Repeated exposure may provide valuable information on stress reactivity in depression. Fifty-nine women (30 inpatients diagnosed with depression and 29 matched controls) underwent two consecutive runs of a mental arithmetic stress paradigm consisting of one baseline and two exposures to control, stress and recovery phases of 5 minutes each, in a case-control design. Subjective stress and electrocardiography were recorded. Variance of heart rate (HR) and root mean square of successive RR interval differences (RMSSD) were analysed using linear mixed models. Overall, physiological parameters (HR, RMSSD) and subjective stress showed a strong group effect (all p<0.001). In both groups, subjective stress and HR increased in response to stress, but the subjective stress levels of patients with depression did not return to baseline levels after the first stressor and for the remainder of the experiment (all p<0.004 compared to baseline). Patients’ HR reactivity responded oppositely: while HR recovered after the first stress exposure, no reactivity was observed in response to the second exposure. These findings may suggest that the often-reported blunted HR/HRV response to stressors results from exhaustion rather than an incapacity to react to stress. The altered HR reactivity could indicate allostatic (over-) load in depression.